Fire safety and evacuation analysis of a passenger ship - Ntounis, Athanasios (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2017)
Simulation of multiple fire and evacuation scenarios at the cabin space of a passenger ship, using the regulations of SOLAS and IMO, with emphasis on the analysis of the location of the fire and the awarness time of passengers.